The Determinants of Pesticide Regulation: A Statistical Analysis of EPA Decision Making - Cropper, Maureen L.; Evans, William N.; Berardi, Stephen J.; Ducla-Soares, Maria M.; Portney, Paul R. (Journal of Political Economy, 1992)
This paper examines the EPA's decision to cancel or continue the registrations of cancer-causing pesticides that went through the special review process between 1975 and 1989. Despite claims to the contrary, our analysis indicates that the EPA indeed balanced risks against benefits in regulating pesticides: Risks to human health or the environment increased the likelihood that a particular pesticide use was canceled by the EPA; at the same time, the larger the benefits associated with a particular use, the lower was the likelihood of cancellation. Intervention by special-interest groups was also important in the regulatory process. Comments by grower organizations significantly reduced the probability of cancellation, whereas comments by environmental advocacy groups increased the probability of cancellation. Our analysis suggests that the EPA is fully capable of weighing benefits and costs when regulating environmental hazards; however, the implicit value placed on health risks–$35 million per applicator cancer case avoided–may be considered high by some persons.